Educational process in the Orthopedics and Traumatology Service; twenty six years later, University Hospital “Dr. Gustavo Aldereguía Lima” - Félix Rafael Rodríguez Fernández; Antonio Leal Olivera; Yanet María Rodriguez Pena; José Ramón Hernández Puerto (Medisur)
With this small historical review we want to acknowledge the work of a group of professors who began teaching at a very young age, since the founding of Higher Medical Teaching in the Medical school Raúl Dorticós Torrado in Cienfuegos, and in the Orthopaedics and Traumatology Service in the University hospital Dr. Gustavo Aldereguía Lima. The first group of Pre and Post Graduated courses began in September, 1st 1982, with the arrival of the first group of fifth year of Medicine from Santa Clara Medical School and the beginning of the residency by Dr. Eduardo Sarmiento Sánchez after an educational accreditation of the Service by a National Commission headed by Professor René Lorie Pérez.